Dramatisme Ikatan Cinta di RCTI “Analisis Terhadap Sinetron Ikatan Cinta Dengan Pendekatan Teori Dramaturgi Erving Goffman” - Wawan Setiawan; Vina Vionita; Erin Alvianita (An-Nahdliyyah: Jurnal Studi Keislaman, 2023)
The existence of the world of television in Indonesia began with the presence of Televisi Republik Indonesia (TVRI), namely as the first television station in Indonesia. This was followed by the emergence of private TV stations such as Rajawali Citra Televisi Indonesia (RCTI), Surya Citra Televisi (CSTV), Indosiar, Trans TV, Trans 7, TV ONE, MNC TV, NET TV, and so on. Of course, with the development of technology and information in the field of television, there have appeared challenges on television shows, both comedies, films, talk shows, music or quizzes and even soap operas. Of the many shows on every television, there is one show that is currently going viral, namely the bond of love among Indonesian people, especially among women. The method used in writing this article is constructivism. Constructivism emphasizes truth in a social reality that can be seen as a social construction. The results of this study indicate that the soap opera Ikatan Cinta from a Dramaturgi perspective is an episode that matches the scenario that has been made as attractive as possible, so that the message to be communicated through verbal and non-verbal discussion on the soap opera Cinta Cinta can be accepted and can even entertain all people. This is in accordance with Dramaturgo Goffman's theory, in which theory it is explained that when interacting he manages messages that he hopes to grow in other people. Humans as actors who are playing a role. In the drama soap opera Ikatan Cinta is seen as a performance, the use of symbols to present a story. A performance of meaning and action is produced in a scene in a sociocultural context.